Adaptation to stress in football athletes: The importance of cognitive appraisal - Gomes, A. Rui; Simães, Clara; Morais, Catarina; Cunha, Ricardo (Frontiers in Psychology, 2022)
This study analysed the adaptation of football athletes to competitive stressors regarding the upcoming match. For that, the study adopted a cross-sectional methodology using a critical incident approach. The participants were 352 young male football athletes, aged between 15 to 19 years (M = 16.91, SD = 0.99), who were competing in the national football championship. The results indicated that cognitive appraisal partially mediated the relationship between competitive stressors and emotions: athletes who perceived stressors as a challenge, tended to feel more control over the situation and more resourceful (coping perception), leading to a more positive emotional experience, while those perceiving the stressors as a threat were more prone to experience less control and more negative emotions. This mediation model was moderated by athletes’ competitive level (U17 or U19), as the role of challenge perception was more pronounced in the U19 team, while the relationship between threat perception and less control was only observed for the U17 team. In sum, the data reveals the importance of cognitive appraisal in young football athletes’ adaptation to competitive stressors, bolstering the theoretical models in this area and the importance of psychologists to consider these variables during intervention, particularly cognitive appraisal.